People's power and government towards the long-term efficacy of a revolutionary tool - Cariño, Ledivina V. (Philippine Journal of Public Administration, 1986)
"People's power" which toppled the Marcos regime at EDSA is briefly traced to previous efforts at conscientization and mobilization. To enhance its long-term effectiveness as a tool of the revolutionary government, attention should be made on how people's power may be manifested. Some suggestions on how government and other institutions may encourage and enhance people's power are advanced. The issues and hard questions raised provide impetus to encourage further dialogue and discussion on how people's power and government may work together for the full realization of democracy and development in the country.